Effect of Yeast Based Biofertilizer combined with bacteria on Mustard Plant Growth - Nur Hidayatul Alami (International Journal of Applied Biology, 2017)
Biofertilizers are commonly defined as microbial inoculants which are capable of mobilizing important nutrient in the soil from non-available to available form for the plants through their biological processes. Hence to increase the productivity of the soil, the use of biofertilizer is necessary. Candida yeast as a phosphate solubilizer and decomposer. Azotobacter bacteria as a nitrogen-fixing bacteria and Bacillus as a phosphate solubilizer. The combination of these microorganisms as biofertilizer needs to be tested its effect against mustard (Brassica juncea L.) plant growth.The results showed that the combination of Bacillus Candida obtained the highest yield among other biofertilizer treatments with a value of 13.6 cm at plant height, 4.96 grams in wet weight and 2.29 grams in dry weight. The combination of Azotobacter Candida showed the highest result on the parameter of width and number of leaves with the values of 20.3 cm and 5.3. Combination of Azotobacter Bacillus Candida showed the highest yield on the root length parameter with a value of 5.0 cm. The addition of biofertilizer is expected to reduce pollution on the soil due to residues produced by chemical fertilizers.Keyword : Azotobacter, Bacillus, Biofertilizer, Candida, Mustard Plant